Off-Grid Photovoltaic (OGPV) System Design for Residential House Using Glide Application - Abd. Halim, Nursyuhani; Mohamad Radzi, Nur Hanis (Evolution in Electrical and Electronic Engineering, 2023)
The challenge from NEM 3.0 after 10 years, the users are not allowed to receive electricity from the grid. The user will have to use the off-grid photovoltaic system known as SELCO because conventional sources of energy were decreased. The costing using conventional energy also was very expensive because extremely high global demand. As an initiative to reduce adverse effects on the environment and reduce costs, the consumer was encouraged to use solar energy and install solar PV. Therefore, the user needs to prepare the equipment which is several batteries, the cost, and the payback period after using the OGPV system or SELCO. This project focuses on the design of an off-grid photovoltaic system for residential houses using the Glide application. The aim is to provide information and requirements for installing OGPV systems or self-consumption (SELCO), considering the challenges presented by Malaysia’s Net Energy Metering (NEM) Scheme and NEM 3.0. The project objectives include determining load requirements, designing system components (including solar PV, charger controller, inverter, and batteries), developing an automatic calculation system with the Glide application, and comparing the results with manual calculations. The research contributes to the advancement of renewable energy adoption and offers sustainable power solutions for residential buildings. The proposed system provides users with a user-friendly interface for obtaining necessary information and assisting in system design. In the research work, an automatic system was developed using the Glide application, allowing users to streamline the installation process for OGPV systems in residential houses. Then, the OGPV system design obtained through the Glide application was compared with the manual calculations to evaluate its effectiveness and efficiency. The knowledge gained from this project will contribute to future generations in the field of OGPV systems.